An overview of the current research on stability of ships and ocean vehicles: The STAB2018 perspective. (15th August 2019) - Manderbacka, Teemu; Themelis, Nikolaos; Bačkalov, Igor; Boulougouris, Evangelos; Eliopoulou, Eleftheria; Hashimoto, Hirotada; Konovessis, Dimitris; Leguen, Jean-François; Míguez González, Marcos; Rodríguez, Claudio A.; Rosén, Anders; Ruponen, Pekka; et al.
Abstract: The paper provides an insight into contemporary research on ship stability and identifies the possible directions for future research by reviewing a selection of papers published in STAB 2015, ISSW 2016 & 2017. These works have been organized in different sections, according to the main thematic areas of research, covering intact and damage stability, regulatory issues including probabilistic approaches, advanced numerical methods for ship motion and stability failure prediction including roll damping, operational issues related to ship stability and environmental modelling. Furthermore, the educational potential of STAB/ISSW is exemplified. This review paper is a joint effort within the SRDC (Stability R&D Committee). Highlights: The manuscript covers the recent research on the stability of ships and ocean vehicles and categorizes it in a useful manner. The most relevant references are presented providing an overview and a starting point to research on the ship stability. The paper exposes the important advances and challenges in the main thematic areas of the research on the stability. The importance of STAB and ISSW for education in ship stability is highlighted.